Synthesis of Pyridines from Acetylene and Ammonia (Eurasian Journal of Engineering and Technology, 2023)
Highly efficient, stable catalysts and technology for 2- and 4-methylpridines from acetylene and ammonia have been developed. Polyfunctional catalysts containing oxides and fluorides of zinc, iron, cadmium, aluminum and other metals are used as contacts.